Sosialisasi Pencegahan Penyalahgunaan Narkoba Sejak Dini di SDN Jatitengah Kecamatan Sugihwaras Kabupaten Bojonegoro - Juliyani, Erly; Amirul Mukminin, Muhammad Diva; Al Khoshi, Muhammad Febby (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Socialization is the process by which individuals acquire the culture of their group and internalize norms their social life to some extent, leading individuals to consider the expectations of others. By holding this seminar, there can be interaction between speakers and students at SDN Jatitengah about the dangers of drugs in children at an early age. Therefore, the work program chosen was a seminar on the dangers of drugs in children at an early age at SDN Jatitengah. This is also to prevent drug abuse in early childhood. Implementation methods include material presentations, seminars on the dangers of drugs in early childhood, question and answer sessions for students as an introduction and providing understanding for students regarding the dangers of drugs for young children and the importance of physical health as well as providing education in the form of information about dealers. and drug users. It can be concluded that after this counseling, students understand and know more about the dangers of drugs and the law for users and dealers.